Nikola Tesla as a phenomenon in the world of science - Slavković, Vukan R (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
This article is dedicated to Nikola Tesla, who created a technically and intellectually highly developed civilization and who is a true companion to humanity in the historical process. The significance of its motives is a need, which drives to the activity towards a specific goal in favour of technical achievements applicable in practice. Of particular importance for understanding Tesla’s actions is a moral awareness that represents the adopted principles of his thoughts that are logical and impeccably clear, and they are the proof that on their basis he made arguments and achieved new results.